Streptococcus pyogenes capsule promotes microcolony-independent biofilm formation - Matysik, Artur (2019)
Biofilms play an important role in the pathogenesis of Group A Streptococcus (GAS), a gram-positive pathogen responsible for a wide range infections and significant public health impact. Although most GAS serotypes are able to form biofilms, there is large heterogeneity between individual strains in biofilm formation, as measured by standard crystal violet assays. It is generally accepted that biofilm formation includes initial adhesion of bacterial cells to a surface, followed by microcolony formation, biofilm maturation, and extensive production of extracellular matrix that links together proliferating cells and provides a scaffold for the three-dimensional biofilm structure. However, our studies show that for GAS strain JS95, microcolony formation is not an essential step in static biofilm formation, and instead, biofilm can be effectively formed from slow-growing or non-replicating late exponential or early stationary planktonic cells, via sedimentation and fixation of GAS chains into biofilms. In addition, we show that the GAS capsule specifically contributes to the alternative, sedimentation-initiated biofilms. Microcolony-independent, sedimentation biofilms are similar in morphology and 3-D structure to biofilms initiated by actively dividing planktonic bacteria. We conclude that GAS can form biofilms by an alternate, non-canonical mechanism that does not require transition from microcolony formation to biofilm maturation, and which may be obscured by biofilm phenotypes that arise via the classical biofilm maturation processes.